Poly[bis(μ-hemihydrogen 2-phenylquinoline-4-carboxylato-κ2N,O)silver(I)]. Corrigendum (Acta Crystallographica Section E, 2009)
The affiliation of one of the authors in the paper by Zhang, Wei & Li [Acta Cryst. (2009), E65, m223] is corrected.